La France et l’Empire d’Autriche 1815–1918 - Horel, Catherine (Balcanica - Annual of the Institute for Balkan Studies, 2007)
France and the Austrian Empire 1815–1918 Relations between France and the Habsburg Empire during the long nineteenth century went through several phases bounded by the events crucial not just to the two countries’mutual relations but to all of Europe.The Congress of Vienna defined their mutual relations for the next thirty years. The Habsburgs and their omnipresent minister Metternich were fearful of revolutionary and liberal movements traditionally having their origins in France. And it was the revolutionary events of 1848 that brought about a change in the balance of power and their mutual relations. Metternich’s retirement and, more importantly, the arrival of the Russian armies in Central Europe and the subsequent strengthening of Prussia, conferred a new importance to the role of the Habsburg Monarchy as a bulwark against the advancement of Russia and a vital counterweight to Prussia. With the defeat of Napoleon III and the creation of Germany with Alsace and Lorraine, Franco-Austrian relations entered a new phase.The destiny of the two provinces alienated the Habsburgs from the French Republic, especially after the reorganization of Europe into two confronting blocs.The logic of alliances led to their being adversaries in the world conflict, although Napoleon III’s geo-strategic analyses remained present almost to its very end, when Clemenceau’s government gave support to the nationality principle thereby crucially contributing to the collapse of the Habsburg Monarchy.